Aï¬€ects of Latrine Ownership to the Community Morbidity in Papua Province: Pengaruh Kepemilikan Jamban terhadap Angka Kesakitan Masyarakat Provinsi Papua - Agus Sumarsono (STIKes Hang Tuah Pekanbaru, 2019)
Papua Revives Mandiri and Prosperity is the aspiration of All Communities in Papua Province, Independence and prosperity can only be realized if the Community Has a Healthy Body and Soul. The degree of health is not only realized by the level of health services, but also influenced by environmental sanitation, including the ownership of latrines as a place to defecate. The Papua Central Bureau of Statistics has presented data related to the Environmental Health and Morbidity Figures data.This study uses a quantitative descriptive approach, with analytical statistics, utilizing available secondary data. The method is used to determine the average latrine ownership number and the average value of morbidity rates according to Kabuopaten City in Papua Province. Furthermore, looking for 3 (three) districts that have the highest and lowest numbers both in terms of toilet ownership and morbidity rates. Furthermore, with the average value of the two variables, you want to know the relationship between the two variables with simple linear regression using the Exel Toolpack. Results: The absence of latrines is related to the number of morbidity obtained by the equation Y = -0.085X + 10.04 and the value of RÂ² = 0.021. Regression test results obtained df = 1 value F = 5.58 with a significant level of 0.025559 which means there is a significant relationship between toilet ownership and morbidity rates